Lab coats in Hollywood : science, scientists, and cinema - Kirby, David A. (David Allen), 1968- (Cambridge, Mass. : MIT Press, 2011)
Stanley Kubrick{u2019}s "2001: A Space Odyssey", released in 1968, is perhaps the most scientifically accurate film ever produced. The film presented such a plausible, realistic vision of space flight that many moon hoax proponents believe that Kubrick staged the 1969 moon landing using the same studios and techniques. Kubrick{u2019}s scientific verisimilitude in 2001 came courtesy of his science consultants{u2014}including two former NASA scientists{u2014}; and the more than sixty-five companies, research organizations, and government agencies that offered technical advice. Although most filmmakers don{u2019}t consult experts as extensively as Kubrick, films ranging from "A Beautiful Mind" and "Contact" to "Finding Nemo and "The Hulk"have achieved some degree of scientific credibility because of science consultants. In Lab Coats in Hollywood, David Kirby examines the interaction of science and cinema: how science consultants make movie science plausible, how filmmakers negotiate scientific accuracy within production constraints, and how movies affect popular perceptions of science.
Scientific expertise in Hollywood : the interactions between scientific and entertainment cultures -- Cinematic science : scientific representation, film realism, and virtual witnessing technologies -- Valuing expertise : the entertainment industry's and scientific community's motivations in the science consulting relationship -- Scientists on screen : being a scientist, looking like a lab -- Cinematic fact checking : negotiating scientific facts within filmmaking culture -- Best guesses : scientific uncertainty, flexibility, and scientists in the aisles -- Fantastically logical : fantastic science, speculative scenarios, and the expertise of logic -- Preventing future disasters : science consultants and the enhancement of cinematic disasters -- The future is now : diegetic prototypes and the role of cinematic narratives in generating real-world technological development -- Improving science, improving entertainment : the significance of scientists in Hollywood.
Includes bibliographical references and index.
Keywords: Science in motion pictures; Scientists in motion pictures